Effect of Partial Span Aspiration on the Performance of a Transonic Axial Compressor Rotor: A Numerical Study - Vijaykumar Jain; Quamber H. Nagpurwala; Abdul Nassar (International Journal of Rotating Machinery)
Aspiration in an axial compressor is normally regarded as sucking out the low momentum boundary layer from blade suction surface, thus lowering the chances of flow separation and consequently that of stall under off-design operation. However, the suction mass flow does not take part in useful work and leads to loss of engine power output. This paper deals with a new concept of natural aspiration to energize blade suction surface boundary layer by injecting some fluid from pressure to suction side through a part span slot on the blade. The energized boundary layer has lesser tendency to separate, thus enhancing stall margin. Numerical simulations were carried out to study the effect of aspiration slot location and geometry on the performance and stall margin of a transonic axial compressor rotor. The computational results without aspiration slot were in fair agreement with the published experimental data. The modified rotor, with part span aspiration, showed ~3.2% improvement in stall margin at design rotational speed. The pressure ratio and efficiency of the aspirated rotor dropped by ~1.42% and ~2.0%, respectively, whereas the structural analysis did not indicate any adverse effect on the blade stress distribution in the presence of aspiration slot.